Standardized hybrid living donor hemihepatectomy in adult‐to‐adult living donor liver transplantation. Issue 3 (9th February 2018) - Eguchi, Susumu; Soyama, Akihiko; Hara, Takanobu; Natsuda, Koji; Okada, Satomi; Hamada, Takashi; Kosaka, Taiichiro; Ono, Shinichiro; Adachi, Tomohiko; Hidaka, Masaaki; Takatsuki, Mitsuhisa
Abstract : The aim of this study was to analyze the outcomes of the most updated version and largest group of our standardized hybrid (laparoscopic mobilization and hepatectomy through midline incision) living donor (LD) hemihepatectomy compared with those from a conventional laparotomy in adult‐to‐adult living donor liver transplantation (LDLT). Of 237 adult‐to‐adult LDLTs from August 1997 to March 2017, 110 LDs underwent the hybrid procedure. Preoperative and operative factors were analyzed and compared with conventional laparotomy (n = 126). The median duration of laparoscopic usage was 26 minutes in the hybrid group. Although there was improvement in applying this procedure over time from the beginning of the series of cases studied, blood loss and operative duration were still smaller and shorter in the hybrid group. There was no significant difference between the groups in the incidence of postoperative complications greater than or equal to Clavien‐Dindo class III. There was no difference in recipient outcome between the groups. Our standardized procedure of hybrid LD hepatectomy is applicable and safe for all types of LD hepatectomies, and it enables the benefit of both the laparoscopic and the open approach in a transplant center without a laparoscopic expert. Liver Transplantation 24 363–368 2018 AASLD.